Is point-of-care testing feasible and safe in care homes in England? An exploratory usability and accuracy evaluation of a point-of-care polymerase chain reaction test for SARS-CoV-2. (21st April 2021) - Micocci, Massimo; Gordon, Adam L; Seo, Mikyung Kelly; Allen, A Joy; Davies, Kerrie; Lasserson, Dan; Thompson, Carl; Spilsbury, Karen; Akrill, Cyd; Heath, Ros; Astle, Anita; Sharpe, Claire; et al.
Abstract: Introduction: Reliable rapid testing for COVID-19 is needed in care homes to reduce the risk of outbreaks and enable timely care. This study aimed to examine the usability and test performance of a point of care polymerase chain reaction (PCR) test for detection of SARS-CoV-2 (POCKIT TM Central) in care homes. Methods: POCKIT TM Central was evaluated in a purposeful sample of four UK care homes. Test agreement with laboratory real-time PCR and usability and used errors were assessed. Results: No significant usability-related hazards emerged, and the sources of error identified were found to be amendable with minor changes in training or test workflow. POCKIT TM Central has acceptable sensitivity and specificity based on RT-PCR as the reference standard, especially for symptomatic cases. Asymptomatic specimens showed 83.3% (95% confidence interval (CI): 35.9–99.6%) positive agreement and 98.7% negative agreement (95% CI: 96.2–99.7%), with overall prevalence and bias-adjusted kappa (PABAK) of 0.965 (95% CI: 0.932– 0.999). Symptomatic specimens showed 100% (95% CI: 2.5–100%) positive agreement and 100% negative agreement (95% CI: 85.8–100%), with overall PABAK of 1. Recommendations are provided to mitigate the frequency of occurrence of the residual use errors observed. Integration pathways were discussed to identify opportunities and limitations of adopting POCKIT™ Central for screening and diagnostic testing purposes. Conclusions: Point-of-care PCR testing in care homes can be considered with appropriate preparatory steps and safeguards. Further diagnostic accuracy evaluations and in-service evaluation studies should be conducted, if the test is to be implemented more widely, to build greater certainty on this initial exploratory analysis.